Fontes de resistência ao oídio em germoplasma de ervilha (Pisum sativum) e caracterização de isolados fúngicos. - PEREIRA, P. R. (2019)
The objectives of the present work were: (1)to evaluate 145 pea accessions in search for new sources of resistance to powdery mildewunder Brazilian conditions; (2)to confirm (via molecular markers) the presence of the powdery mildew resistance loci er1, er2 andEr3in the evaluated germplasm and (3)to characterizethe fungal isolates that were able to breakdown the resistance in accessions previously identified as sources of resistance to this disease in Brazil.